2017
DOI: 10.1186/s13640-017-0212-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of motion history image variants for video-based depression assessment

Abstract: Depression is the most prevalent mood disorder and a leading cause of disability worldwide. Automated video-based analyses may afford objective measures to support clinical judgments. In the present paper, categorical depression assessment is addressed by proposing a novel variant of the Motion History Image (MHI) which considers Gabor-inhibited filtered data instead of the original image. Classification results obtained with this method on the AVEC'14 dataset are compared to those derived using (a) an earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Additional studies have detected attention deficit hyperactivity disorder from gestures and body movements [367]. Such differences have been used to diagnose mental health problems [375], [376]. See Table 7 for more details about differentiating clinical disorders from healthy controls.…”
Section: Emotion and Mental Healthmentioning
confidence: 99%
“…Additional studies have detected attention deficit hyperactivity disorder from gestures and body movements [367]. Such differences have been used to diagnose mental health problems [375], [376]. See Table 7 for more details about differentiating clinical disorders from healthy controls.…”
Section: Emotion and Mental Healthmentioning
confidence: 99%
“…A number of roadblocks, however, are hindering the development of these technologies. Deep emotion analysis algorithms are often based on very short consecutive segments, often just a single frame [42]. Therefore, the prediction of behavior can be quite inaccurate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the review of the literature for depression detection, the techniques suggested can be categorized as unimodal and multi-modal. Uni-modal techniques are the ones that involve judgement/analysis based on a single modality: only video [2][3][4], only text [5][6][7], or only speech [8][9][10]. Multi-modal techniques, which are a hybrid of two or more modalities (videos, speech, and text) together [11][12][13] have been proposed to improve the performance further.…”
Section: Introductionmentioning
confidence: 99%